Rock Glacier Kinematics in the Valles Calchaquíes Region, Northwestern Argentina, From Multi‐Temporal Aerial and Satellite Imagery (1968–2023) - Blöthe, Jan Henrik (2024)
In semiarid mountain ranges, rock glaciers constitute an important part of the periglacial environment. However, quantitative data on the state of rock glacier activity remain scarce. Here, we derive kinematic information on rock glaciers located in the Valles Calchaquíes region (24–25° S) in Argentina from optical feature tracking in historical aerial photographs, ALOS PRISM, and CBERS-4A imagery for 175 landforms between 1968 and 2023. To overcome matching difficulties resulting from varying image quality and lighting conditions, we make use of directional filters to enhance feature-tracking performance. We find the mean surface velocities exceeding the limit of detection (LoD) of our analysis to fall between 0.28 and 0.70 m yr−1 for all three epochs. Automatically deriving moving areas (MAs) with homogeneous flow fields from our data, we find between 46% and 25% of MAs are exceeding the LoD of our analysis. Analyzing data that covers more than five decades, we find largely unchanged rock glacier velocities, despite significant warming documented for the region. Our study provides the first quantitative information on rock glacier kinematics for multiple landforms in the Desert Andes of Argentina, contributing important information to assess the impacts of climate warming on this remote periglacial environment.